Evaluating paper-based TOEFL preparation program using the Context, Input, Process, and Product (CIPP) model - Abdul Manan; Muhammad Arif Fadhilah; Kamarullah Kamarullah; Habiburrahim Habiburrahim (Studies in English Language and Education, 2020)
An evaluation for the development of a paper-based test of English as a Foreign Language (TOEFL) for English Education Department students at one of the colleges in Langsa, Aceh, Indonesia, is necessary, considering their unsatisfactory scores even though the preparation program has been conducted. This research employed context, input, process, and product (CIPP) model developed by Stufflebeam upon the program. Methodologically, interviews, questionnaires, and observation were executed to five TOEFL lecturers and 34 students, while the data obtained were analyzed with the qualitative analysis method of Miles and Huberman. Based on the evaluation of context, the program had an appropriate background, goals, and objectives. Regarding the input, it still had problems related to the availability of resources and facilities. There were no standardized learning materials available, including the broken language laboratory. It affected the process since the lecturers could not maximize the facilities to create an effective learning environment. Eventually, it affected the product since most students could not reach an expected score. Most of the participants agreed that the program needed to be improved. Several improvements can be made to overcome these problems by providing required learning facilities, designing standardized learning materials, and clustering classes in accordance with students’ abilities.